War in the Ukrainian fields: The weaponization of international wheat trade - Fabio Parasecoli; Mihai Varga (economic sociology. perspectives and conversations, 2023)
The cost of food rose all over the world in 2022. The spike in the prices of bread was swift and shocking, partly because of its symbolic value in many countries and its importance as a staple, which turns its scarcity into a political issue. This phenomenon is particularly worrisome in low-income countries that import large amounts of wheat and where bread and flour constitute an important percentage of populations' daily food expenses.
Keywords: 300